Application of pyritic sludge with an anaerobic granule consortium for nitrate removal in low carbon systems. (1st February 2022) - Pelivano, Bojan; Bryson, Samuel; Hunt, Kristopher A.; Denecke, Martin; Stahl, David A.; Winkler, Mari
Highlights: Competitive behavior between denitrification and DNRA over methanogenesis. Iron sulfide and pyrite formation based on hydrolysis activity in granule. FeS precipitates in form of onion layers with function of electron shifting stations. Cycling electron activity between iron and sulfur elements. Equivalent electron mass balance for granule provided. Abstract: Granules recovered from a highly reduced anaerobic digester were capable of active nitrogen removal in the absence of exogenous electron donors, averaging 0.25 mg mgNO3 − -N /gVSS/d over 546 days of operation. Electron mass balance indicated that about half the influent nitrate was converted to ammonia via DNRA and another half denitrified. This capacity was associated with an onion-like structure of multiple layers enriched in reduced iron and sulfur, and a complex microbial community shown by metagenomic sequencing to consist of multiple physiological groups and associated activities, including methanogenesis, denitrification, dissimilatory nitrate reduction to ammonia (DNRA), iron oxidation and reduction, and sulfur reduction and oxidation. Nitrate reduction was supported by both entrained organic material and reduced iron and sulfur species, corresponding to 2.13 mg COD/gVSS/d. Batch incubations showed that approximately 15% of denitrified nitrate was coupled to the oxidation of sulfur derived from both sulfate respiration and granular material enriched in iron-sulfide. Inhibition of sulfate reduction resulted in redirection of electron flow to methanogenesis and, in combination with other batch tests, showed that these granules supported a complex microbial community in which cryptic redox cycles linked carbon, sulfur, and iron oxidation with nitrate, sulfate, iron, and carbon dioxide reduction. This system shows promise for treatment of nitrate contaminated ground water without addition of an external organic carbon source as well as wastewater treatment in combination with (granular) sludge elimination leading in a net reduction of solid treatment costs. Graphical abstract: Image, graphical abstract .